Hydropower - Breeze, Paul (Academic Press [Imprint] San Diego : Elsevier Science & Technology Books Oxford : Elsevier Science & Technology [Distributor], 2018)
Annotation 'Hydropower' provides a complete discussion of the most up-to-date considerations of this method of creating renewable energy. After introducing the method's history, the author explores various considerations for engineers, planners and managers who need to determine the best placement and size of a plant. The book then presents various types of hydropower systems, such as Run-of-River Schemes and various types of Dam and Turbines, also considering the important economic, environmental and geological impacts of each. Those involved in the planning, design and management of hydropower systems, such as engineers, researchers, managers and policymakers will find this book a very valuable and insightful resource.
Scholarly & Professional